5th Nordic Forum for Nurse Educators. Current Trends and Innovation in Nurse Education - Mažionienė, Asta; Andruškienė, Jurgita (Slauga. Mokslas ir praktika, 2020)
Klaipeda State University of Applied Sciences in collaboration with MEDICO, Nordic Collaboration Network for Nursing Medication Educators, a Nordplus Higher Education Network has organized 5th Nordic Forum For Nurse Educators „Current Trends and Innovation in Nursing Education on 10th of November, 2020 m. The aim of the Forum is to share experience in nursing practice and education in the process of nurses education development in Nordic countries. The main themes of the Forum covered Interprofessional Collaboration in Nursing Education, Learning Technology in Nursing Education, Clinical Internship Evaluation in Nursing Edu-cation and Nursing Education and Curriculum Development. It was concluded that nurses play an extremely important role in responding appropriately to the new challenges when the world is facing threatening infectious diseases outbreaks. The nursing profession must produce leaders throughout the health care system, from the bedsite to the boardroom. It is recommended to integrate collaborative learning into nursing education due to the positive influences on student learning and studying outcomes. Nursing educators should create interdisciplinary educational experiences for students to better prepare them for their roles in a clinical setting. Nurse educators play a significant role in integration of innovative eLearning techno-logies as well as artificial intelligence in continuing nursing education. There were 29 presentations of nurse educators representing Nordic countries, including Sweden, Norway, Fin-land, Estonia, Latvia and Lithuania. All participants are welcome to the 6th Nordic Forum for Nurse Educators in Turku (Finland) in 2020.